Innovation Dynamics and Business Growth in Philippines’ Micro, Small, and Medium-Sized Enterprise Bakeries: The Moderating Role of Entrepreneurial Experience in Product and Process Innovations - Abellana, Jupert Jasser; Jegonia, Joey Marie f.; Alonzo, Albert A. (International Review of Management and Marketing, 2026)
This study examines how process and product innovation drive business growth in MSME bakeries, with entrepreneurial experience as a moderating factor. Data from 227 respondents, analyzed using PLS-SEM, shows that process innovation improves efficiency, reduces costs, and boosts productivity, contributing to business growth. Product innovation also enhances growth by helping businesses adapt to consumer preferences and differentiate offerings. Entrepreneurial experience strengthens the link between process innovation and growth indicating that industry expertise enhances operational improvements. However, its effect on product innovation is insignificant, which suggests that other market factors play a greater role. MSME bakeries must invest in automation and workflow optimization to improve efficiency and conduct market research to align products with consumer trends such as health and sustainability. Business owners enhance innovation strategies through continuous learning via mentorship and industry networks. Policymakers provide support through financial aid and technical training. Future research explores factors such as digital transformation and technological adaptation to develop a better understanding of how innovation drives business growth.